Pasteurização de salsichas com ultrassom e micro-ondas - Rampelotto, Cristine (2012)
This study aimed to develop new methods for pasteurization of sausages with the use of ultrasound and microwaves in order to reduce the bacterial load with more energy efficient and low impact on the characteristics of the product. For pasteurization with microwave oven, sausages were divided into 22 groups, of which one was the control that not received treatment, and the others received treatment in a microwave in different conditions, varying the time and power. The effect of the microwave treated sausage was evaluated with and without a water bath, in the presence or absence of packaging. Sausages treated with microwave unwrapped in conditions that do not change visually, reduced mesophilic and acid lactic bacteria statistically significant, but at a rate not significant for practical use. When treated were packaged, it was observed that the packaging commonly used in sausage has little resistance to microwave pasteurization, and breaks observed in some cases. It was necessary to use a water bath to maintain maintain package integrity. The data obtained on the sausage pasteurization with microwave suggest that are required the development of suitable packaging and adapting the machine to produce more uniform heating and controlled. For pasteurization with ultrasound were analyzed the effectiveness of the frequencies of 25 kHz and 130 kHz in the reduction of mesophilic bacteria and acid lactic bacteria and the effect of frequency on color, lipid oxidation and pH. We evaluated the potential bactericidal effect of ultrasound of 25 kHz on pathogenic bacteria Staphylococcus aureus and Bacillus cereus and the effect of storage on the microbiological aspects, lipid oxidation, color, pH and texture of pasteurized sausages with ultrasound. The frequency of 25 kHz, was more effective in reducing mesophilic bacteria and acid lactic bacteria and not changing color and pH, as well as producing lower lipid oxidation. The ultrasound effect was observed on the destruction of Bacillus cereus and apparently did not affect the cells of Staphylococcus aureus. For the avaluated storage conditions, ultrasound promoted inhibition of acid lactic, psychrotrophic and mesophilic bacteria and lower lipid oxidation up to 60 days of storage, with minimal color and pH change, without affecting the texture.